Autograph letter signed from Beethoven to Sigmund Anton Steiner, Vienna, February 1822 [Brandenburg no. 1502] - Beethoven, Ludwig van, 1770-1027 (sender):::Creator::::::::::::; Steiner, Sigmund Anton, 1773-1838 (recipient):::Contributor:::::::::::: (Austria; Vienna, 2021)
Autograph letter signed from Beethoven to his publisher Sigmund Anton Steiner in Vienna requesting a copy of his cantata for chorus and orchestra, "Meeresstille und glückliche Fahrt" ("Calm Sea and Properous Voyage"), Opus 112, which Steiner published in February 1822. The text of the cantata is by Johann Wolfgang von Goethe, to whom Beethoven dedicated the work. One half page, in German with signature in Latin script, with address and remnant of a red seal on verso. Translation from Anderson: "Please send me one copy of Meeresstille und glückliche Fahrt and so forth for what has been promised; and at the same time I undertake to correct the proofs in a few days. I am terribly busy and at the moment have no one to help me. With the sincerest sincerity yours, Beethoven.